Gross Abnormalities of Abattoir Derived Ovine Reproductive Tract in Jammu Region
An abattoir survey of abnormalities of the genital tracts of 556 ewes in Jammu region of the Jammu and Kashmir was undertaken. Pregnancy was detected in 13.31 % of tracts, while 35.07% were found to be abnormal with gross lesions. The highest number of abnormalities were found in ovaries (13.66%) followed by uterus (11.33%) and least in oviducts (10.07%). The most common abnormalities in ovaries were parovarian cysts (5.75%), followed by follicular cysts (4.67%), luteal cysts (2.87%) and ovarobursal adhesions (0.35%). Among the oviductal abnormalities, adhesions (4.67%) were found to be the highest, followed by salpingitis (3.41 %) and hydrosalpinx (1.97%). Endometritis was found to be chief reproductive abnormality comprising 8.63% of the uterine abnormalities, followed by pyometra (1.61 %) and hydrometra (1.08%